Hamka’s Doctoral Address at Al-Azhar: The Influence of Muhammad Abduh in Indonesia - Kevin W. Fogg (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2015)
This is a translation of the doctoral address given by Haji Abdul Malik Karim Amrullah (Hamka) when he received a doctorate honouris causa from al-Azhar University. Although Hamka assigned his talk the title ‘The Influence of Muham- mad Abduh in Indonesia’, the primary topic is actually the evolution of Islam in Indonesia and the development of Islamic reformism and the address minimally touches on the Egyptian thinker. For the 1950s, this can be taken as a normative, indigenous view of Indonesia in an Islamic, especially reformist, context